THE EFFECT OF DELIVERY SERVICES ON CONSUMER LOYALTY OF ARTHA BIMA MALL IN THE COVID-19 PANDEMIC - Sumiati Sumiati; Irma Mardian (Universitas Muhammadiyah Makassar, 2022)
This study aims to determine the effect of delivery services on consumer loyalty at Artha Bima Mall during the Covid-19 pandemic. This type of research is associative using quantitative data from primary data sources. The research instrument used was a questionnaire with a Likert scale. The population in this study are all consumers of Artha Bima Mall who use delivery services, the number is not known with certainty (unknown population) so that the sample in this study was 64 respondents using accidental sampling technique. Data collection techniques used in this study were observation, interviews, questionnaires and literature study. The data analysis technique used in this research is validity test, reliability test, simple linear regression analysis, simple correlation coefficient, determination test and t test. The results showed that there was an influence of delivery services on the loyalty of Artha Bima Mall consumers during the Covid-19 pandemic with a very strong level of influence.